The Effect of Economic Growth and Inflation on Poverty In The Province of The Sulawesi Region for The 2012-2021 Period - Dai, Sri Indriyani S.; Abdul, Irawati; Apuadji, Wahyu; Katili, Annisa Pratiwi (Proceedings of International Conference of Graduate School on Sustainability, 2025)
This study aims to determine the influence of Economic Growth and Inflation on Poverty in the provinces of the Sulawesi regional region. The data used in the study is secondary data in the form of 6 provinces for ten years, namely from 2012 to 2021, sourced from the Central Statistics Agency. The method used is multiple regression analysis using panel data using the Random Effect Model (REM). The results of the analysis show that 1) The Economic Growth variable has a positive but insignificant effect on poverty, meaning that every 1 percent increase in Economic Growth can increase poverty. However, Economic Growth has not been able to explain the Poverty variable in a real way. 2) Inflation has a positive and significant effect on poverty, meaning that every 1 percent increase in inflation can increase poverty in the Sulawesi Region. 3) Economic growth and inflation also jointly affect poverty. It was concluded that economic growth